A unifying biology of sex steroid-induced apoptosis in prostate and breast cancers. Issue 2 (February 2018) - Maximov, Philipp Y; Abderrahman, Balkees; Curpan, Ramona F; Hawsawi, Yousef M; Fan, Ping; Jordan, V Craig
Abstract : Prostate and breast cancer are the two cancers with the highest incidence in men and women, respectively. Here, we focus on the known biology of acquired resistance to antihormone therapy of prostate and breast cancer and compare laboratory and clinical similarities in the evolution of the disease. Laboratory studies and clinical observations in prostate and breast cancer demonstrate that cell selection pathways occur during acquired resistance to antihormonal therapy. Following sex steroid deprivation, both prostate and breast cancer models show an initial increased acquired sensitivity to the growth potential of sex steroids. Subsequently, prostate and breast cancer cells either become dependent upon the antihormone treatment or grow spontaneously in the absence of hormones. Paradoxically, the physiologic sex steroids now kill a proportion of selected, but vulnerable, resistant tumor cells. The sex steroid receptor complex triggers apoptosis. We draw parallels between acquired resistance in prostate and breast cancer to sex steroid deprivation. Clinical observations and patient trials confirm the veracity of the laboratory studies. We consider therapeutic strategies to increase response rates in clinical trials of metastatic disease that can subsequently be applied as a preemptive salvage adjuvant therapy. The goal of future advances is to enhance response rates and deploy a safe strategy earlier in the treatment plan to save lives. The introduction of a simple evidence-based enhanced adjuvant therapy as a global healthcare strategy has the potential to control recurrence, reduce hospitalization, reduce healthcare costs and maintain a healthier population that contributes to society.